C-reactive protein and procalcitonin during course of sepsis and septic shock: original article - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Dudda, Jonas; Brück, Lea Marie; Hoffmann, Ursula; Bertsch, Thomas; Akın, Ibrahim; Behnes, Michael (Irish journal of medical science, 2024)
The study investigates the diagnostic and prognostic value of C-reactive protein (CRP) and procalcitonin (PCT) in patients with sepsis and septic shock.